Profil dan Kontribusi Ibn Saâd dalam Kajian Hadis Sîrah - Nirwana, Dzikri (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2013)
Historically, the study of hadith in Islam emerged as the study of sîrah. Both of these disciplines appear as awareness and concern of the classical Muslim scholars to the purity and preservation of the historical mission of the Prophet Muhammad. The contribution of hadith to the formation of Islamic historiography in general, is not only just limited to the provision of material which is enormous for writing sîrah, but also has implications for the formation of Islamic historiography writing methods, such as the method isnâd as a character of hadith expert, and the chronological method as the character of historians. Al-Tabaqât al-Kabîr by Ibn Saâd (w. 230 H.) is considered as a pioneering work that elaborates on two systems. Even when viewed as an integrative, the works of Ibn Saâd regarded as the only one pioneering work who elaborates three forms of historiography at once (sîrah, maghâzî, and asmÃ¢â al-rijâl). Collaborative forms of Islamic historiography in the works of Ibn Saâd is certainly a new breakthrough in the classical historiography art which is in previously only in fragmentary form.